An Analysis of Code-Mixing and Code-Switching Used By An English Teacher and Students In EFL Classroom in Sumedang - Tinanthy Rosse Santosa; Rahma Sakina; Eva Meidi Kulsum (Gunung Djati Conference Series, 2023)
Code-switching and code-mixing are phenomenon which is influenced by the bilingualism of someone or a speech community. The bilingualism is also affected by globalization which makes a lot of information and knowledge available to everyone in the world. The study background is the code-switching and code-mixing phenomenon occurs both in formal or informal situation, including in English for Foreign Language classroom where people learn English to gain more wide information and knowledge. The aims of this research are to identify the types of code-switching and code-mixing and which type is dominantly used by teacher and students in EFL classroom. The study used a descriptive qualitative method to analyse the choice code phenomenon used by teacher and students in EFL classroom under study. The theory used to analyse the code-switching and code-mixing are the three types of code-switching by Poplack (1980) and the three types of code-mixing by Muysken (2000). As the result there are found that the type of code-switching mostly used is the inter-sentential switching in case to clarify the meaning of target language by switching to the first language. And the type of code-mixing mostly used is the insertion which occurs consciously to mention some point in target language